SEJARAH PERADABAN ISLAM DI CINA DAN NILAI-NILAI PENDIDIKAN ISLAM DALAM NOVEL ASSALAMUALAIKUM BEIJING - Widada, Dwi Masdi (J-PAI: Jurnal Pendidikan Agama Islam, 2016)
The phrase that describes that a science should be pursued even to China. Novel Assalamualaikum Beijing provides an overview of the presence of Islam in the Bamboo Curtain country. Islamic civilization has appeared some time ago in China. The novel is intentionally prove that Islam was, and triumphed in China. Islam not only had triumphed in Europe, especially Andalusia (now Spain). Travelling around the main character of China as a columnist Asma Indonesia provided a glimmer of hope, strength, and love of the teachings of Islam. Islam never lived and interacted with the people of China. Chinese Muslim faces with hoods and eyes sipitnya show relationships and interactions among the Muslims. Islam in China is known as "pure religion of the sky" .In this novel, the reader is also treated to the values of Islamic education, the history of Islam, and the messages of Islam. Building a mosque in China a sign of the existence of Islam. One of the mosques and Muslim villages in China. This shows the triumph of Islam in the past. The value of education and the propagation of Islam seen in self Zhongwen figures. He was fascinated with friends Mus'ab bin Umair handsome and willing to remove the sparkling world for his new love in IslamÂ Keywords: Islamic Civilization, Islamic Education Value, China